Pengaruh Penambahan Polyvinyl Alcohol (PVOH) pada Biofoam dari Tepung Biji Nangka dan Ampok Jagung dengan Metode Thermopressing - Fitrianti, Yanis; Azzahra, Rheisya Talitha; Kusumawati, Endang; Keryanti (Talenta Publisher (Universitas Sumatera Utara), 2023)
Starch and fiber-based biofoam as a solution to replace the role of styrofoam. However, the biofoam still unqualified as a good foam characteristic. Polyvinyl alcohol (PVOH) is added to improve the physical characteristics of biofoam. This study aims to determine the effect of PVOH addition on the quality of starch-based biofoam from jackfruit seeds and corn hominy. The gelatinization process was carried out using a mixer in 350 rpm speed at 100 °C for 5 minutes, then moulded in a thermopressing unit for 25 minutes at 100 °C. The characteristics of the material with amylose and amylopectin contents 17.30% and 31.60% respectively and corn hominy's fiber content at 2.72%. The best PVOH addition was 10% addition based on its characteristics from parameters such as water absorption, density, and biodegradability were close to Synbra Technology’s standard. However, all the physical and mechanical characteristics of the produced biofoam still can't reach the standard.